CORRECTION OF RED BLOOD INDICATORS WITH CONTINUOUS COMBINED EFFECT OF LOW INTENSITY IONIZING RADIATION - Коваленко, Поліна; Ракша-Слюсарева, Олена; Слюсарев, Олексій; Тур, Ярослава (SWorldJournal, 2023)
The features of the radiomodification effect of the biologically active additive (BAA) mumijo on the state of red blood indicators of 53 conditionally healthy women (UZH) – volunteers aged 33-52 years, living in Kropyvnytskyi under the conditions of cons